Facts and Fictions: Focusing on TripAdvisor Reviews of Mount Tangkuban Parahu - Aditya Rizki Rinaldi (Jurnal Internasional Penelitian Bisnis Terapan, 2023)
Folklore as a form of intangible cultural heritage can be used as a strong cultural capital for tourism development. The existence of the legend of Sangkuriang, which is thick among the Sundanese community, and other aspects such as geological and volcanological aspects become tourism strengths of Mount Tangkuban Parahu. Using content analysis on traveler reviews on TripAdvisor pages, this article explores how "Sangkuriang'' affects travelers. The word mining technique on TripAdvisor reviews from 2011 to 2021 shows several frequently appearing topics in the reviews. Furthermore, the network visualization shows that words with folklore connotations are often related to the landscape of this mountain. In other words, the presence of folklore is depicted physically in a narrative. However, some reviewers see this mountain from its physical sides, such as the beauty of the scenery and the presence of a crater that emits a sulfur smell. The findings of this study show that travelers tend to process factual and fictional information simultaneously and share it as information in their reviews.